Prevalence and Factors Associated with Musculoskeletal Pain among Rural Handloom Weavers in Sirajganj, Bangladesh (Bangladesh Pharmaceutical Journal, 2022)
The loom industry is the traditional industry in Bangladesh. It is situated especially in rural areas. Many weavers are working in the handloom industry. The study aims to determine the prevalence rate of musculoskeletal pain and its associated factors. This study is a cross-sectional study, including openended and close-ended questionnaires. Two hundred fifty (250) handloom weavers have participated in this study. Frequency analysis and Chi-square test were done by R software. A total of 82.4% of weavers have musculoskeletal pain. Among them, 50% have lower back pain, 48.4% have shoulder pain, and 46.4% have knee pain. Some factors are associated with those pain. Age of respondents and number of working days are associated with lower back pain and shoulder pain. Only age is associated with thigh, ankle and elbow pain. Types of treatment that weavers have taken are associated with arm pain. The weavers with musculoskeletal pain are mostly illiterate and have not taken physical exercise. Notably, 67.2% of weavers have taken treatment, and 21.6% of the participants reported that they have improved upon the treatment. Among those who have taken treatment, only 21.6% of weavers have got improved. As the highest portion of weavers has musculoskeletal, proper knowledge should be implemented for them and need to improve their quality of life. Bangladesh government and any Non- Governmental Organizations (NGOs) or institutions should implement consciousness about musculoskeletal pain.Bangladesh Pharmaceutical Journal 25(2): 188-198, 2022 (July)